PENGGUNAAN MEDIA GARISMATIKA SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PADA MATA PELAJARAN MATEMATIKA - Paramita, Destri; MS, Zulela; Noornia, Anton (Jurnal Pendidikan Dasar, 2018)
Abstract: This research aims to improve the understanding the concept of multiplication by using the media garismatika in mathematics class III Elementary School in West Palimanan Cirebon in the academic year 2016/2017. The results showed that the study of mathematics by using garismatika media to enhance understanding of the concept of multiplication. This is indicated from the observed activities and positive response from the students' research subjects and also students overall to the learning of mathematics by using garismatika media. As well as by an increase in score of understanding the concept of multiplication on the subject of research in each indicator and the value end of the cycle test all students in grade III. The increase in value in the first cycle the number of students who were able to achieve success indicator is only 57.70% of the students, and increased in the second cycle into 84.61% of students. Keywords: Understading The Concept, Multiplication and Media Garismatika.